The Alien Tort Statute from the Perspective of Federal Court Procedure - John N. Drobak (Washington University Global Studies Law Review, 2014)
"This Article will examine a number of procedural issues relevant to the Alien Tort Statute, focusing on what the Supreme Court has resolved and what remains open for future litigation. It will analyze the constitutional basis for the Statute and explain how the law of nations, as part of federal common law, established the decision rules for ATS litigation. Then it will examine the meaning of the territoriality limitation imposed by Kiobel in the context of the Court’s established practice of interpreting jurisdictional statutes narrowly. After looking at the relevance of recent changes in personal jurisdiction law for ATS suits, the Article will examine statutes of limitations and tolling rules, forum non conveniens, exhaustion of remedies, and comity. It will conclude with consideration of the issues that remain to be answered by future litigation under the Statute."
Keywords: exhaustion of remedies; comity; forum non conveniens; federal common law; personal jurisdiction; ATS; Alien Tort Statute; Kiobel; Filartiga; constitution; constitutional; procedure; statute of limitations; toll; tolling; jurisdiction